Aligning Development Aid toward Sustainable Development Goals: When and Where is Aid Effective on the Health Workforce? - Yong Wang; Sandun C. Perera; Sachin K. Mangla; Linna Han; Malin Song (Prod. Oper. Manag., 2024)
Ensuring universal health coverage is one of the top priorities under the United Nations' Sustainable Development Goals (SDGs). The World Health Organization recognizes the critical role of the health workforce in promoting this mission. However, developing countries throughout the world often experience shortages in the health workforce, especially during pandemic outbreaks such as coronavirus disease 2019. Governments and humanitarian organizations worldwide have supported health workforce development through development aid, but many questions remain about its effectiveness. Therefore, this study investigates whether development aid is effective toward health workforce growth, in general, and when and where the aid is effective within various segments of the health workforce, in particular. Furthermore, the study explores the role of government behavior in recipient countries and the introduction of SDG-3 on aid effectiveness for the health workforce. Analyzing data pertaining to 134 developing countries using fixed-, moderating-, threshold-effects regression models and event study methods, we derive the following results: First, all forms of development aid contribute positively to the health workforce from a universal perspective. Second, we establish that aid can be an effective catalyst for physicians and clinical officials and the total health workforce only when the current workforce density of the corresponding workforce segment exceeds a certain threshold. Thus, countries with severe shortages in the total health workforce as well as physicians and clinical officials, have difficulty reaping the dividends of health personnel development aid. Fortunately, we find a breakthrough from the perspective of nurses and midwives wherein the development aid is shown to be always effective for this leading segment of the health workforce. Finally, it is shown that increased government health expenditure, government effectiveness of recipient countries, and the introduction of SDG-3.c significantly enhance aid effectiveness. Our study directly benefits funding managers with development aid allocation and implicitly enhances donor recognition and confidence in health personnel development aid, thereby supporting the universal health coverage goals of the United Nations and the World Health Organization.
Keywords: Blockchain; Personal health records; Health information interoperability; Precision health care; Health information management